2020
DOI: 10.24127/ajpm.v9i2.2824
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Modul Teori Peluang Untuk Meningkatkan Hasil Belajar Dan Disposisi Matematis

Abstract: Penelitian ini bertujuan untuk mengembangkan Modul Pembelajaran Mata Kuliah Teori Peluang untuk mahasiswa Pendidikan Matematika yang valid, praktis dan efektif. Jenis penelitian ini adalah penelitian pengembangan (Research & Development). Penelitian ini mengembangkan modul mata kuliah dengan menggunakan model pengembangan 4D (Define, Design, Develop, Dessiminate) yang dikembangkan oleh Thiagarajan, Dorothy S. Semmel, dan Melvyn I Semmel. Instrumen penelitian yang digunakan terdiri dari lembar validasi yang dii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
5
0
5
Order By: Relevance
“…A module in the learning process also provides opportunities for students to work together with their peers (Junaida et al, 2016). And the existence of a learning module will make students learn difficult material (Nurmeidina et al, 2020). Several module development studies have been carried out, among others, research conducted by Faidah et al, (2019) found that the mathematics module based on Howard Gardner's Theory of Multiple Intelligences Using the Realistic Mathematics Education (RME) approach on the material cubes and blocks that have been developed is feasible to use.…”
Section: The Effectiveness Of the Learning Modulementioning
confidence: 99%
See 1 more Smart Citation
“…A module in the learning process also provides opportunities for students to work together with their peers (Junaida et al, 2016). And the existence of a learning module will make students learn difficult material (Nurmeidina et al, 2020). Several module development studies have been carried out, among others, research conducted by Faidah et al, (2019) found that the mathematics module based on Howard Gardner's Theory of Multiple Intelligences Using the Realistic Mathematics Education (RME) approach on the material cubes and blocks that have been developed is feasible to use.…”
Section: The Effectiveness Of the Learning Modulementioning
confidence: 99%
“…A module in the learning process also provides opportunities for students to work together with their peers (Junaida et al, 2016). And the existence of a learning module will make students learn difficult material (Nurmeidina et al, 2020). The advantages of this learning module are the reason some researchers have developed learning modules.…”
Section: Introductionmentioning
confidence: 99%
“…Draft ini akan digunakan untuk proses uji coba lapangan. Sesuai dengan penelitian (Nurmeidina, R., Lazwardi, A. & Ariyanti, 2020;Qomario et al, 2014) Rata-rata seluruh bab 3,81…”
Section: Deskripsi Tahap Perancanganunclassified
“…Based on the interview results, it was also found that students were not used to and motivated to work on problems with problem-solving abilities; they tended to give up first before trying to answer and preferred to do routine questions about understanding concepts only. In higher education, lecturers play an essential role in providing facilities or conditioning lectures with the right method, one of which is doing modules [7].…”
Section: Introductionmentioning
confidence: 99%